The Role of Religious Education in Installing Social Awareness Among Students: Peran Pendidikan Agama dalam Menanamkan Kesadaran Sosial Di Kalangan Siswa - Hilmi, Fuad; Habibah, Eulis; Suhana, Dede; Nurlalela, Ela; Hakim, Lukman; Maryana, Ina (Edukasi: Journal of Educational Research, 2024)
Social awareness is an individual's ability to understand and respond positively to social situations. In the context of education, instilling social awareness in students is very important because it can form the best generation in the future. This research aims to find out how religious education at Syahida Vocational School instills awareness social among students. This research uses descriptive qualitative methods with purposive sampling to select research subjects. Data was collected through interviews, documentation and observation, with research subjects consisting of school principals, student affairs, religious education teachers and students. Data analysis techniques include collecting, reducing, presenting and verifying data. The results of the research show that religious education at Syahida Vocational School has succeeded in instilling social awareness in students, which can be seen from changes in students' attitudes to become more empathetic, tolerant, caring, communicative, responsible and sensitive. This is verified through a data assessment rubric which includes the results of observations, interviews and documentation. The conclusion of this research is that religious education has a very large role in increasing students' social awareness.